2016
DOI: 10.1016/j.engfailanal.2015.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion process between a fibre mooring line and a corroded steel element during the transit and commissioning of a marine renewable energy device

Abstract: SummaryThis paper brings together two experiences from TTI (Tension Technology International) and the UoE (University of Exeter) and aims to quantify the damage that could be experienced by fibre mooring lines during the transit and commissioning phase of Marine Renewable Energy (MRE) devices.1. While deploying a new prototype of anchoring system for a MRE device, UoE experienced the failure of a new polyester mooring line during transit to site (90 minute duration). A thorough visual inspection supported by S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Note that it is the internal abrasion that generates heat in the rope such that the fibers melt together, reducing the strength of the rope. Herduin, Banfield, Weller, Thies, and Johanning (2016) show through experimental tests that there is a linear relationship between the strength loss due to external abrasion and the surface roughness.…”
Section: Damage Mechanisms For Fiber Ropesmentioning
confidence: 93%
“…Note that it is the internal abrasion that generates heat in the rope such that the fibers melt together, reducing the strength of the rope. Herduin, Banfield, Weller, Thies, and Johanning (2016) show through experimental tests that there is a linear relationship between the strength loss due to external abrasion and the surface roughness.…”
Section: Damage Mechanisms For Fiber Ropesmentioning
confidence: 93%
“…Castillo et al (2020) have confirmed that synthetic fiber ropes serve as optimization tools for achieving a cost-effective and reliable mooring system design [1]. Synthetic fiber ropes are advantageous in terms of reduced corrosion problems, with wet polyester experiencing lower abrasion rates compared to dry polyester ropes, as proposed by Herduin et al (2016) [16]. However, it is crucial to note several adverse effects associated with synthetic fiber ropes.…”
Section: Synthetic Fiber Ropesmentioning
confidence: 99%